Comparative properties of bacteriophage phi6 and phi6 nucleocapsid. - Etten, J V (1976)
Nonionic detergent treatments released a nucleocapsid from the enveloped bacteriphage phi6. The nucleocapsid sedimented at nearly the same rate as the whole phage in sucrose density gradients, but the buoyant density in Cs2S04 changed from 1.22 g/cm3 for the whole phage to 1.33 g/cm3 for the nucleocapsid. The detergent completely removed the lipid and 5 of the 10 proteins from the phage. Surface labeling of the phage and nucleocapsid with 125I revealed that protein P3 was on the outer surface of the whole phage and P8 was on the surface of the nucleocapsid. Both the phage and the nucleocapsid were stable between pH 6.0 and 9.5. Low concentrations of EDTA (10-4 M) dissociated the nucleocapsid but had no effect on the whole phage. The nucleocapsid contained all three double-stranded RNA segments, as well as RNA polymerase activity.